User benefit analysis of main pedestrian bridges in Kuantan Town Centre - Nor Aisahton, Junet (2012)
As a developing country, a smooth transportation system is one of the main factors that we should be concerned in attracting foreign investors, thus increasing the economic potential of our country. The traffic volume has increase year by year and one of the solutions for this issue is by increasing the number of lane for congested road network However by doing so, it will give high risk for pedestrian to cross the road and the heavy traffic flow could also be contributed to more accidents involving pedestrians. Pedestrian bridge is one of the important structures to be constructed especially in urban areas where traffic volume is high. Unfortunately, the pedestrian bridge that has been built is not fully utilized by pedestrians and become a wastage. Pedestrians usually prefer to cross at-grade rather than choosing the bridge. Therefore, this study is set to identify the effectiveness of pedestrian bridges in Kuantan Town Centre and to analyze the miss opportunity factors by Cost Benefit Analysis approach. Two bridges located at Jalan Tun Ismail and Jalan Mahkota had been chosen and one collected for traffic volume, pedestrian volume and questionnaire analysis on users' opinion.